a=radical din 2 -1
b=radical din 2 +1
calculati 1 supra a + 1 supra b
Răspunsuri la întrebare
Răspuns de
4
a = √2 - 1
b = √2 + 1
1 / a = 1 / √2 - 1
1 / b = 1 / √2 + 1
1 / a + 1 / b = 1 / √2 - 1 + 1 / √2 + 1 = (√2 - 1) - (√2+ 1) / (√2 - 1) · (√2 + 1) = (√2 - 1 + √2 - 1) / (√2² + √2 + √2 - 1) = 2√2 / (2 + 2√2 - 1)
b = √2 + 1
1 / a = 1 / √2 - 1
1 / b = 1 / √2 + 1
1 / a + 1 / b = 1 / √2 - 1 + 1 / √2 + 1 = (√2 - 1) - (√2+ 1) / (√2 - 1) · (√2 + 1) = (√2 - 1 + √2 - 1) / (√2² + √2 + √2 - 1) = 2√2 / (2 + 2√2 - 1)
Alte întrebări interesante
Matematică,
9 ani în urmă
Fizică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Franceza,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă